2021
DOI: 10.1186/s12862-021-01762-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of PEBP family genes in nine Rosaceae tree species and their expression analysis in P. mume

Abstract: Background Phosphatidylethanolamine-binding proteins (PEBPs) constitute a common gene family found among animals, plants and microbes. Plant PEBP proteins play an important role in regulating flowering time, plant architecture as well as seed dormancy. Though PEBP family genes have been well studied in Arabidopsis and other model species, less is known about these genes in perennial trees. Results To understand the evolution of PEBP genes and their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 149 publications
(107 reference statements)
3
16
0
Order By: Relevance
“…BjBFT1 was detected in all tissues but showed relatively high expression in the root, stem, and leaf. This finding is consistent with that of a previous study by Zhang et al [ 36 ] who stated that BFT expression is relatively high in the stem and leaf of Prunus yedoensis and Rosaceae occidentalis . In Arabidopsis sp., MFT4 plays a redundant role in flowering [ 9 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…BjBFT1 was detected in all tissues but showed relatively high expression in the root, stem, and leaf. This finding is consistent with that of a previous study by Zhang et al [ 36 ] who stated that BFT expression is relatively high in the stem and leaf of Prunus yedoensis and Rosaceae occidentalis . In Arabidopsis sp., MFT4 plays a redundant role in flowering [ 9 ].…”
Section: Discussionsupporting
confidence: 94%
“…Regarding the structural composition of PEBP , all PEBP genes were found to have four exons and three introns, except BjMFT1 and BjPYBHB1 ; this finding is consistent with that of Zhang et al [ 36 ] who identified the PEBP gene family in nine Rosaceae trees species. The second and third exons of BjPEBP were noted to be short and the first and fourth exons were noted to be long; this finding is similar to that observed in Jatropha curcas [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Using the chilling hour model, we calculated total chilling hours (CH) required for cultivar "Subaitage" as approximately 320 CHs, which started to accumulate since October 12th, 2020 (Figure 1B). In P. mume, floral organ initiation was induced in late summer with floral primordium continuing to develop throughout winter (Zhang et al, 2021a). In early November, floral buds were maintained in endodormant state with floral organ primordiums, including sepal, petal, stamen, and pistil fully differentiated.…”
Section: Physiological Changes During Floral Bud Breakmentioning
confidence: 99%